Host mobility key management in dynamic secure group communication - Daghighi, Babak; Mat Kiah, Miss Laiha; Iqbal, Salman; Rehman, Muhammad Habib Ur; Martin, Keith (Springer Verlag, 2018)
The key management has a fundamental role in securing group communications taking place over vast and unprotected networks. It is concerned with the distribution and update of the keying materials whenever any changes occur in the group membership. Wireless mobile environments enable members to move freely within the networks, which causes more difficulty to design efficient and scalable key management protocols. This is partly because both member location dynamic and group membership dynamic must be managed concurrently, which may lead to significant rekeying overhead. This paper presents a hierarchical group key management scheme taking the mobility of members into consideration intended for wireless mobile environments. The proposed scheme supports the mobility of members across wireless mobile environments while remaining in the group session with minimum rekeying transmission overhead. Furthermore, the proposed scheme alleviates 1-affect-n phenomenon, single point of failure, and signaling load caused by moving members at the core network. Simulation results shows that the scheme surpasses other existing efforts in terms of communication overhead and affected members. The security requirements studies also show the backward and forward secrecy is preserved in the proposed scheme even though the members move between areas.